2019
DOI: 10.1021/acscatal.9b02282
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Composition-Promoted Electrocatalytic Hydrodechlorination Reaction on Silver–Palladium Alloy Nanoparticles

Abstract: Studies of the electrocatalytic hydrodechlorination (EHDC) reaction using monodisperse AgPd nanoparticle (NP) model catalysts in the present work reveal the essential role of the catalytically inert Ag component in promoting bimetallic nanocatalyst's activity for the conversion of 2,4-dichlorophenol (2,4-DCP) to phenol (P). The EHDC reaction rate, current efficiency, and product selectivity were systematically investigated, leading to the observation of a volcano-type activity dependence on the Ag content in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 42 publications
5
78
0
Order By: Relevance
“…The Ag was anticipated to promote Pd performance for furfural electrocatalytic reduction, as our previous studies revealed that Pd was subject to over-strong adsorption of aromatic entities and could be effectively modulated by Ag alloying. 10 Similar effects have been observed in recent reports where AgPd nanoalloys were used as catalysts in different electrochemical systems. 11,12 The results herein demonstrate that bimetallic AgPd alloy nano-Scheme 1 Summary of furfural production and common electrochemical reduction products derived from furfural.…”
supporting
confidence: 82%
“…The Ag was anticipated to promote Pd performance for furfural electrocatalytic reduction, as our previous studies revealed that Pd was subject to over-strong adsorption of aromatic entities and could be effectively modulated by Ag alloying. 10 Similar effects have been observed in recent reports where AgPd nanoalloys were used as catalysts in different electrochemical systems. 11,12 The results herein demonstrate that bimetallic AgPd alloy nano-Scheme 1 Summary of furfural production and common electrochemical reduction products derived from furfural.…”
supporting
confidence: 82%
“…Another is hydrodehalogenation of the atomic hydrogen species produced on the metal surface that trigger the C-X bond cleavage. 5,46,47 This could be described as follows:…”
Section: Effect Of Ph On Electroreductive Dehalogenationmentioning
confidence: 99%
“…In this regard, dual-metal sites with different metallicities and d orbitals can induce polarization in N 2 molecules to a larger extent (Figure 1B). [31][32][33] Therefore, constructing dual-metal sites could provide new opportunities to develop highly efficient catalysts for N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%